Hypoglycaemic and Antioxidant Potency of Momordica Charantia, Strobilanthes Crispus and Their Combination in Alleviating Alloxan-Induced Injuries in Rats - Mohammad, Noor Azlina (2006)
In an attempt to find a less toxic and easily available oral hypoglycaemic agent,two herbs were selected. The oven-dried fruits Momordica charantia (M) and oven-dried leaves Strobilanthes crispus (S) were incorporated into the feed of rats at 5% inclusion level.A total of 72, six weeks old male Sprague Dawley rats were used whereby eight rats each were assigned to each group.The group receiving normal pellet served as the control (N) while diabetes mellitus was induced by an intraperitoneal injection of alloxan monohydrate.Thus,the groups of rats were as follows; control (N),Momordica only (M),Strobilanthes only (S) M plus S (MS), diabetic (D), D plus glibenclimide (DG),D plus M (DM),D plus S (DS) and D plus M plus S (DMS).The experiment was carried out for 24 weeks following one week period of acclimatasation. At all instances,water and feed were given ad libitum. The rats were monitored daily for the development of abnormal clinical signs.Body weight was taken triweekly and simultaneously blood was also taken. Blood taken were subject to glucose, malondialdehyde (MDA), gluthatione peroxidase (GSH-Px),superoxide dismutase (SOD) and catalase (CAT) assays. At the end of the study, all rats were killed and the liver,kidney, heart, eye and pancreas were taken for histopathologic examination and scoring. Data obtained were subjected to the general linear model statistical (GLM) analysis.The study showed that alloxan was able to induce hyperglycaemia in rats. Likewise, it was found that M and S were able to alleviate hyperglycaemic-induced injuries in rats.These includes a much lower blood glucose, decreased MDA levels, increased GSH-Px and SOD activities and minimal tissue changes. The changes are more pronounced when both herbs were used in combination and is believed to act synergistically.The study also showed that MDA is a reliable and sensitive indicator of peroxidation status while GSH-Px and SOD are excellent biomarkers of antioxidant status.The prolong use of both herbs did not result in any deleterious effects in both the euglycaemic and hyperglycaemic groups